Peran Strategis Retorika Dakwah dalam Membangun Komunikasi Politik yang Efektif di Masyarakat Muslim Indonesia - Batubara, Jihan Afri; Katimin; Samosir, Hasrat Efendi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the role and urgency of da'wah rhetoric in political communication in Indonesia, with a focus on the context of the Muslim-majority society. As an art of communication, da'wah rhetoric has evolved into a tool for building relationships between leaders and the public, both in spiritual and socio-political dimensions. In this study, the author employs a qualitative approach with a literature review as the primary method, relying on written sources such as books, articles, and previous research to explore the concepts of da'wah rhetoric and its application in political communication. The findings of this study show that da'wah rhetoric not only serves to strengthen religious identity but also functions as a strategic means of shaping public opinion and advancing public agendas, using moral and religious values that can influence the feelings and emotions of the audience. The study discusses three methods of da'wah rhetoric: the method of hikmah (wisdom), mau'izhah hasanah (good advice), and mujadalah billati hiya ahsan (debate in the best manner). The application of these methods is crucial for delivering political messages effectively and persuasively.